SURVEI ATTITUDE DAN MOTIVASI PADA ATLET ASJAD BADMINTON CLUB - Suhardimansyah, Muhammad Riedho; Rubiyatno, Rubiyatno; Perdana, Rahmat Putra (Universitas Tanjungpura, 2024)
This study aims to determine and analyze the attitudes and motivations of ASJAD Badminton Club athletes. This study uses a survey method with a quantitative descriptive approach, where data is collected through a questionnaire distributed to 20 ASJAD Badminton Club athletes. The questionnaire used consists of items related to attitudes towards training, competition, and coaches, as well as intrinsic and extrinsic motivation in achieving. The results of the study showed that in the attitude category, 6 athletes received a score of